Adaptive grading systems, or pros and cons of different ways of grading grammar exams - Richard Skultety Madsen (Globe, 2019)
This paper investigates several alternatives to the grading system used currently when examining students’ knowledge of theoretical grammar in the Department of English Business Communication at Aalborg University, Denmark. The proposed alternatives differ from the current system in two parameters, namely by differentiating between exam questions according to their levels of difficulty and by evening out biases which are due to the differences in the weights of the various topics of the exam. It is found that the proposed methods would yield results significantly different from the current grading method even though it would only be in the favor of few students in terms of better grades to adapt any of them. Nevertheless, the study reveals prevalent traits of the current way of examining, such as built-in bias and the scalability of the questions, which are important considerations to anyone conducting exams, not just in grammar. Furthermore, the paper uncovers unexpected features of clause constituents that may have serious implications for their teaching.